Correction: Supramolecular assemblies constructed from inverted cucurbit[7]uril and lanthanide cations: synthesis, structure and sorption properties. Issue 86 (2nd September 2016) - Li, Qing; Qiu, Sheng-Chao; Zhang, Yun-Qian; Xue, Sai-Feng; Tao, Zhu; Prior, Timothy J.; Redshaw, Carl; Zhu, Qian-Jiang; Xiao, Xin
Abstract : Correction for 'Supramolecular assemblies constructed from inverted cucurbit[7]uril and lanthanide cations: synthesis, structure and sorption properties' by Qing Li et al., RSC Adv., 2016, 6, 77805–77810.